Deep Convection Along the Continental Slope in the East/Japan Sea: A Large-Eddy Simulation Study - Kim, Bong-Gwan; Cho, Yang-Ki; Noh, Yign (Frontiers in Marine Science, 2022)
Sparse observations in the East/Japan Sea (EJS) suggested that open-ocean deep convection occurs south of Vladivostok; however, more recent observations suggest that deep convection occurs along the continental slope, resulting in bottom water formation in the EJS. We investigated the process of deep convection along the EJS continental slope using large-eddy simulation (LES), which demonstrated that dense water, formed by strong wintertime cooling in the shelf, flows down along the slope as a bottom Ekman current. The characteristics of the initial dense water were relatively well conserved on the continental slope during convection, but they changed rapidly by mixing with the surrounding waters in the open ocean. Accordingly, slope convection penetrated deeper compared to open-ocean convection under the same surface heat flux. Our numerical experiments showed that, under typical surface cooling during winter (i.e., 200 W m–2), slope convection reaches depths greater than 2,700 m, generating a potential ventilation process for deep- and bottom-water formations, whereas open-ocean convection reaches approximately 700 m depth, contributing to the intermediate- and central-water formations in the EJS. Various topography experiments revealed that downward speed was proportional to the continental-slope inclination; the initial characteristics remained relatively well conserved at a small continental-slope inclination. Increased salinity due to brine rejection in the shelf could accelerate the slope convection.